PENGARUH INFLASI DAN RETURN ON EQUITY TERHADAP RETURN SAHAM - Waskito, Meindro; Pratama, Rio Ananda (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2020)
The purpose of this study was to determine the effect of inflation and return on equity (ROE) on stock returns of manufacturing companies in the food and beverage sub sector in Indonesia in 2014-2019. The sample used in this study is annual data from 2014 - 2019. Hypothesis testing uses panel data regression analysis. The population in this study are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in the period 2014 - 2019. The data used are secondary data with the documentation method. Before analyzing the data, a classic assumption test is held which consists of a normality test, a multicollinearity test, a heteroscedasticity test and an auto correlation test. The analytical method used is panel data regression analysis. Based on the results of data analysis and discussion, inflation does not have a significant negative effect on the stock returns of the manufacturing companies in the food and beverage sub sector and return on equity (ROE) has a significant positive effect on the stock returns of the manufacturing companies in the food and beverage sub sector.